PENATAAN KAWASAN SUNGAI GAJAH WONG SISTEM UTILITAS LINGKUNGAN PERMUKIMAN PENGGAL JEMBATAN WINONG - JEMBATAN TEGALGENDU - , Muh.Zandaru Budi Purwanto, S.T; , Ir. T. Yoyok Wahyu Subroto, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The banks of the River on one side is the river green space, on the other hand banks of a river is an area that for some communities is considered to be a decent place to live Although physically the land relatively steep riverbanks and vulnerable to flooding and landslides as well as the conditions of existence of the narrow alleys that are prone to fire hazard. The Bank of the Gajah Wong River on the territory of the city has developed into a dense settlement along with urbanization of the population that is growing by leaps and bounds. The settlements in this region grows not planned so that less qualified as living quarters for the people.The Bank of the Gajah Wong River included in the waterside area of grow is not planned. Several theories related to the Setup and system utilities settlement used to analyze environmental problems in the region..The method in this research is the deductive approach to rationalistic Unitarians qualitative and quantitative methods of finding problems in the field, compiling the research framework, process data quantitatively to determine the qualitative results. Results of analysis showed that the settlement area of the river environment utility Gajah Wong River viewed from a sanitation network elements and Communal Sanitary Facility, IPAL is still less able to serve the entire population. While the open green space and recreational park the river and is the elements can still be developed to support citizen interaction and comfort environment. The clean water network need to be developed, kemenerusan road environment needs to be improved either North or South to connect both sides of the banks of the river.System utilities environmental settlements on the banks of Gajah Wong River have been formed that are affected by many factors and it is still possible to be developed to support the health and comfort of the environment.